Technology Entrepreneurship Project (ENT 600) : Sony Corporation / Nur Fadzilah Mohd Puad - Mohd Puad, Nur Fadzilah (2021)
This project is an attempt to know how the theories can be applied to a practical situation. As a student in UiTM Arau, it is a part of a learning for everybody to perform a case study project. So, for this purpose, I got the opportunity to do a research on company which manufactured the same product that I want to develop, which is Sony Corporation Sony Corporation is a Japanese multinational conglomerate corporation headquartered in Kōnan, Minato, Tokyo. The company operates as one of the world's largest manufacturers of consumer and professional electronic products, the largest video game console company, the second largest video game publisher, the second largest record company, as well as one of the most comprehensive media companies, being the largest Japanese media conglomerate by size overtaking the privately held, family-owned Yomiuri Shimbun Holdings, the largest Japanese media conglomerate by revenue. One of their focused products is the Sony Walkman In the first part of the study, I found that several problems that slowed down the business of Sony Xperia 5. My focused is on Sony Xperia 5. Those problem are the software of the sony still need to work. Other than that, fingerprint sensor is miss that means cannot detect and lastly, front camera are not satisfied for the consumer who had it. At the end of the study, I performed a SWOT analysis to detect this kind of problems. I recommend Sony to make innovation at Xperia 5 with fingerprint sensor change to voice sensor to unlock the phone. This is suitable for the blind person who use the phone and make easy for them to unlock their phone using the voice sensor.